NICE update NICE public health guidance update. (28th December 2019) - Roberts, Susan; Nolan, Kay; Shearn, Peter; Raynor, Michael; Leng, Gillian
Abstract: This article covers recently published National Institute for Health and Care Excellence (NICE) guidance relevant to public health and a review of evidence published since we released the NICE guidance on unintentional injury prevention in under 15 year olds. The article features some of this evidence that was found to reinforce published recommendations on safety in the home and on the roads, indicating the guidance remains up to date and relevant. In addition, it importantly highlights that there is great opportunity to prevent future unintentional injury through integrated and coordinated, evidence and intelligence-informed approaches.